Impact of body mass index and gender on quality of life in patients with gastroesophageal reflux disease - Lee, Shou-Wu (Baishideng Publishing Group Co., Limited, 2012)
AIM: To investigate the symptom presentation and quality of life in obese Chinese patients with gastroesophageal reflux disease (GERD). METHODS: Data from patients diagnosed with GERD according to the Montreal definition, were collected between January 2009 to March 2010. The enrolled patients were assigned to the normal [body mass index (BMI) < 25 kg/m(2)], overweight (25-30 kg/m(2)), and obese (BMI > 30 kg/m(2)) groups. General demographic data, endoscopic findings, and quality of life of the three groups of patients were analyzed and compared. RESULTS: Among the 173 enrolled patients, 102, 56 and 15 patients were classified in the normal, overweight, and obese, respectively. There was significantly more erosive esophagitis (73.3% vs 64.3% vs 39.2%, P = 0.002), hiatal hernia (60% vs 33.9% vs 16.7%, P = 0.001), and males (73.3% vs 73.2% vs 32.4%, P = 0.001) in the obese cases. The severity and frequency of heartburn, not acid regurgitation, was positively correlated with BMI, with a significant association in men, but not in women. Obese patients were prone to have low quality of life scores, with obese women having the lowest scores for mental health. CONCLUSION: In patients with GERD, obese men had the most severe endoscopic and clinical presentation. Obese women had the poorest mental health.